2019
DOI: 10.1016/j.apenergy.2019.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and deactivation mechanisms of pyrolysis chars from bio-waste during catalytic cracking of tar

Abstract: • Waste-derived char was used as catalyst for tar cracking at different temperatures. • Chars from food waste and sludge are more efficient than wood-based chars. • Char deactivation was due to coke deposition and minerals melting/sintering. • Deactivation mechanism depends on the physicochemical properties of the chars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 69 publications
0
20
1
Order By: Relevance
“…Proper activation temperature was selected as 750 °C, based on facts that higher temperatures lead to pore sintering, while lower temperatures lead to slower micropore development [28][29][30]. Additionally, 750 °C is a temperature low enough to ensure that the inorganic species in the char matrix will not migrate to the surface and block the char pores [11]. On the other hand, the activation time was chosen as 2 hours to ensure sufficient micropore area, because the activation reaction rate with CO2 is known as lower than that with steam [24,31,32].…”
Section: Catalyst Preparation and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Proper activation temperature was selected as 750 °C, based on facts that higher temperatures lead to pore sintering, while lower temperatures lead to slower micropore development [28][29][30]. Additionally, 750 °C is a temperature low enough to ensure that the inorganic species in the char matrix will not migrate to the surface and block the char pores [11]. On the other hand, the activation time was chosen as 2 hours to ensure sufficient micropore area, because the activation reaction rate with CO2 is known as lower than that with steam [24,31,32].…”
Section: Catalyst Preparation and Characterizationmentioning
confidence: 99%
“…Table 2 presents the BET surface areas, average pore diameter, micropore area and micropore volume of the chars before and after 3 hours of use. The surface characteristics of the chars from references [11,14,20] are also included for comparison purposes (see section 4). Expectedly, the activated char exhibited a higher initial micropore area, specific surface area and average micropore diameter than the regular char.…”
Section: Surface Functional Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, there is a relationship between the pore sizes and the catalyst resilience. It has been found that while mesopores do not contribute as much as micropores to provide a high initial tar conversion, they are more resilient to coke and increase the lifespan of the catalyst [131].…”
Section: Use Of Regular Char As a Catalystmentioning
confidence: 99%